Genetic evaluation of F2 inbred strain of Swiss albino mice by microsatellite markers - KAUSHAL, SHOBHANA; KUMAR, PUSHPENDRA; KUMAR, AMIT; SAINI, B L; TARANG, MITEK; CHAUHAN, ANUJ; PRAKASH, JAI; BHUSHAN, BHARAT (The Indian Journal of Animal Sciences, 2021)
Genetic characterization of F2 inbred Swiss albino mice was done using 11 microsatellites markers (D1Mit15, D2Mit51, D2Mit61, D3Mit15, D3Mit55, D5Mit18, D7Mit323, D8Mit14, D9Mit27, D10Mit180, and D11Mit167). The results indicated that genotypic frequencies at all the loci were in Hardy-Weinberg disequilibrium (P